Surface alloying of Ti-6Al-4V using Cu-TaC composite electrode during electrical discharge machining - Mohammed Baba, Ndaliman; Khan, Ahsan Ali; Ali, M. Y. (2011)
This paper presents investigation on the alloying capability of Cu-TaC electrode during electrical discharge machining (EDM). The electrode produced through powder metallurgy technique was used in machining alpha-beta titanium alloy (Ti-6Al-4V) under different machining conditions. EDM experiments were conducted with distilled water as dielectric fluid. The peak current range of 3.5-5.5A and pulse duration of 3.3 - 5.3μsec were the machining conditions used as variables, while other conditions remained constant. The outputs of this investigation are surface composition, topography and surface roughness of the machined surface. The SEM/EDX results indicate that the machined surface was alloyed with carbides and oxides. Both the topography and surface roughness were found to have been affected by the machining conditions of current and pulse duration.